Neutrino Spectroscopy Can Probe the Dark Matter Content in the Sun - Lopes, I (2012)
After being gravitationally captured, low-mass cold dark-matter particles (mass range from 5 to ~50 × 109 electron volts) are thought to drift to the center of the Sun and affect its internal structure. Solar neutrinos provide a way to probe the physical processes occurring in the Sun’s core. Solar neutrino spectroscopy, in particular, is expected to measure the neutrino fluxes produced in nuclear reactions in the Sun. Here, we show how the presence of dark-matter particles inside the Sun will produce unique neutrino flux distributions in 7Be-ν and 8B-ν, as well as 13N-ν, 15O-ν, and 17F-ν.